STRATEGI GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SMA NEGERI 9 MAKASSAR - Nurahryani, Nurahryani; Syamsu K; Ahlun Ansar (Nusantara Hasana Journal, 2025)
This study examines teacher strategies for improving student discipline at SMA Negeri 9 Makassar, as well as supporting and inhibiting factors. The objective of the study was to determine the strategies used by teachers and identify factors influencing the successful implementation of discipline. The study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing, and its validity was tested through technical triangulation. The results indicate that teacher strategies include: (1) role modeling through consistent and transparent rule enforcement; (2) positive habits through active communication, two-way interaction, and parental involvement; and (3) gradual rule enforcement according to the level of violation using a personal and collaborative approach. Supporting factors for discipline include teacher-student cooperation and the availability of a rules book as a guide. Inhibiting factors include a lack of parental involvement, differences in student character, and external environmental influences.